Climate policy uncertainty and green bond markets - Omer Serkan Gulal; Mert Topcu; Furkan Emirmahmutoglu; Abdikani Farah Daud (Environmental Research Communications)
Using monthly data from July 2013 to April 2023, this study applies a time-varying causality approach to examine the relationship between climate policy uncertainty and the green bond market. During the episode December 2016 - December 2018, a negative bi-directional relationship is found, suggesting that higher green bond returns contributed to a reduction in policy uncertainty, fostering a more stable investment environment. However, during the COVID-19 pandemic, the relationship shifted, showing that increased green bond returns were associated with higher CPU, reflecting investor concerns about regulatory responses in times of crisis. Overall, the study emphasizes the importance of considering the time-varying nature of the CPU-green bond nexus while developing consistent and supportive climate policies to sustain the growth of green finance.